2018
DOI: 10.1177/1548051818813091
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling How Coworkers and Supervisors Influence Employee Cyberloafing: What Normative Information Are Employees Attending To?

Abstract: Cyberloafing—the use of an electronic device at work for an activity that an immediate supervisor would not consider work-related—is now the most common way that employees waste time at work. It is well established that social norms play a role in cyberloafing, but it is unknown what specific normative information employees attend to when deciding whether or not to cyberloaf. In Study 1, we tested which of four types of normative information could underlie the observed correlation between social norms and cybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 59 publications
(111 reference statements)
2
56
0
4
Order By: Relevance
“…Likewise, a positive relationship between norms and technology use was also reported in some studies (Schepers & Wetzels, 2007;Teo & van Schaik, 2012). In the same line, research also supports the positive link between cyberloafing and descriptive and prescriptive norms (Askew et al, 2014;Askew et al, 2019) as well as the link between cyberloafing and descriptive and prescriptive norms with respect to both superiors and co-ordinates (Askew et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Likewise, a positive relationship between norms and technology use was also reported in some studies (Schepers & Wetzels, 2007;Teo & van Schaik, 2012). In the same line, research also supports the positive link between cyberloafing and descriptive and prescriptive norms (Askew et al, 2014;Askew et al, 2019) as well as the link between cyberloafing and descriptive and prescriptive norms with respect to both superiors and co-ordinates (Askew et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
“…Indeed, a positive association between behavioral intentions and actual and perceived technology use have been reported by studies undertaken in the educational contexts (Schepers & Wetzels, 2007;Scherer, Siddiq, & Tondeur, 2019;Szajna, 1996). Moreover, intention to cyberloaf was also determined to be a positive correlate of cyberloafing behavior (Askew, Buckner, Taing, Ilie, Bauer, & Coovert, 2014;Askew, Ilie, Bauer, Simonet, Buckner, & Robertson, 2019).…”
Section: Introductionmentioning
confidence: 78%
“…For instance, individuals learn to behave through observations of others' behaviour (Bandura, 1988). Previous research has also consistently demonstrated that co-workers act as referents for employees' cyberslacking/deviance (Ehrhart and Naumann, 2004; Askew et al , 2018; Leasure and Zhang, 2018). Inspired by interpersonal behaviour theory, Koay (2018) has demonstrated the moderating role of constructive work environments on cyberslacking, as such environments provide unfavourable conditions for deviant behaviours.…”
Section: Hypotheses Developmentmentioning
confidence: 91%
“…Blanchard and Henle (2008) described cyberloafing behavior as "cyberslacking" (p. 1068), whereas Alder et al (2008) described cyberloafing and cyberslacking separately but the difference seemed to be blurred (p. 482). Askew et al (2019) included in their definition the perception of "immediate supervisor" for labeling an activity as cyberloafing (p. 526). Weatherbee and Kelloway (2006) acknowledged inconsistent use of different terminologies pertinent to this behavior but also noted that cyberloafing term was used particularly when "organizational internet" is used for personal reasons (p. 36).…”
Section: Introductionmentioning
confidence: 99%